The Authority to Discipline the Public Employee between the Administration and the Judiciary - Hussein, Salma Gadban; Hamood, Husham Mohammed (Indonesian Journal of Law and Economics Review, 2023)
This article presents a comprehensive analysis of disciplinary authorities in public employment, focusing on the diverse factors influencing their establishment and functioning. The study examines the impact of social, political, and economic factors on the choice of disciplinary authority, ranging from administrative bodies to the judiciary. By analyzing various legislations and their associated disciplinary systems, the article highlights the advantages and disadvantages of each approach. The research emphasizes the importance of maintaining a balance between protecting employees' rights and ensuring effective disciplinary measures. Additionally, it stresses the significance of aligning the chosen disciplinary system with the prevailing social, economic, and political conditions. The study concludes by emphasizing the need for periodic evaluation of disciplinary systems to ensure their efficacy and the preservation of public job interests. The findings and implications presented in this article provide valuable insights for policymakers, legal experts, and professionals in the field of public employment, encouraging informed decision-making and promoting effective disciplinary practices. Highlights : The article explores the factors influencing the establishment of disciplinary authorities in public employment, considering social, political, and economic factors. It analyzes the advantages and disadvantages of different disciplinary systems, including administrative bodies and the judiciary. The study emphasizes the importance of maintaining a balance between protecting employees' rights and ensuring effective disciplinary measures. Keywords : Disciplinary Authorities, Public Employment, Administrative Bodies, Judiciary, Effective Disciplinary Practices